2011
DOI: 10.1039/c0lc00672f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube based separation columns for high electrical field strengths in microchip electrochromatography

Abstract: Electrically insulated carbon nanotube (CNT) based separation columns have been fabricated that can withstand an electrical field strength of more than 2.0 kV cm(-1) without bubble formation from electrolysis. The carbon nanotubes were grown in a pillar array defined by photolithographic patterning of the catalyst layer used for synthesis of the nanotubes. Multiwall carbon nanotubes are inherently electrically conductive and cannot be used as a continuous layer in the microfluidic channels, without short circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Since the group of Regnier first used perfectly ordered pillars as the stationary-phase support structure in chromatography in 1998 [2], pillar array columns (PACs) have been studied intensively by a limited number of research groups [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A dramatic reduction of the disorder related eddy dispersion or A-term of the van Deemter equation has been consistently demonstrated throughout the past decade, but also the freedom in external porosity, flow-through pore shape and channel depth turned out to be features that can be exploited to further tune and improve the column considerably.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the group of Regnier first used perfectly ordered pillars as the stationary-phase support structure in chromatography in 1998 [2], pillar array columns (PACs) have been studied intensively by a limited number of research groups [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A dramatic reduction of the disorder related eddy dispersion or A-term of the van Deemter equation has been consistently demonstrated throughout the past decade, but also the freedom in external porosity, flow-through pore shape and channel depth turned out to be features that can be exploited to further tune and improve the column considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom up approaches enable creation of porous layers of another material on pillars. Techniques to use carbon nanotubes (CNTs) for PACs have been developed by the group of Kutter [4,5] and the group of Vinet [16,17], and their work has shown that CNTs can be used as a stationary phase in reversed phase CEC and LC. The use of CNTs is quite unique in the field of chromatography, on the other hand, silica, a traditional material in this field, is often selected as the material of the porous layers prepared by bottom up approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the measurements, the microfluidic channels were filled with a 50 % 10 mM Tertraborate buffer (pH = 9.2) / 50 % acetonitrile solution. For pillar length of 8.0 µm, E can be applied up to 2 kV/cm without bubble formation, which was same as the one measured from the channel without CNTs [9]. Higher E will result in faster fluid flow velocity and smaller plate height, thus making the chips have sharp emission peak and better separation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The chip was successfully tested to isolate a glycosylated protein using concanavalin A immobilized onto the nanotube bed. Moreover, immobilization of the CNTs enabled the application of a notably high electrical field strength, thereby eliminating bubble formation .…”
Section: Improvement Of Ce Separationmentioning
confidence: 99%